Environmental Influence Work and Communication on Work Stress and Employee Performance Inna Bali Heritage Hotel - Gde A. Prabhawatya Jyotisanta; Ni Putu Nina Eka Lestari; A A Ngr. Oka Suryadinatha G; A A Ngr. Eddy Supriyadinatha G (Dinasti International Journal of Education Management And Social Science, 2025)
Currently, Hotel Inna Bali Heritage is facing various dynamics that affect the company's performance. In an effort to optimize performance and address market challenges, strategic management approaches have become essential and cannot be overlooked. This study aims to explore the impact of the work environment and communication on employee job stress and performance at Hotel Inna Bali Heritage. Using a quantitative approach with inferential statistical analysis, the study found that a comfortable and safe work environment has a negative and significant impact on employee job stress, meaning that good facilities can reduce stress levels. Effective communication between management and employees, as well as among coworkers, was also found to reduce job stress, with results indicating that smooth communication creates a more comfortable environment and minimizes confusion. Furthermore, the study results show that a supportive work environment significantly improves employee performance, with employees working in more comfortable conditions demonstrating higher levels of productivity. Clear and open communication also contributes to improving employee performance by helping them understand tasks and expectations. However, the study also found that high job stress negatively affects employee performance, as high levels of stress reduce employees' ability to work effectively.